UJI AKURASI MESIN PENERJEMAH STATISTIK (MPS) BAHASA INDONESIA KE BAHASA MELAYU SAMBAS DAN MESIN PENERJEMAH STATISTIK (MPS) BAHASA MELAYU SAMBAS KE BAHASA INDONESIA - Hadi, Ibnu (Jurusan Informatika Universitas Tanjungpura, 2014)
Language is an important means ofcommunication for humans, because language make wecan find out the information that we need, at other side wecan convey our ideas. With the rapidly development of technology in all sectors, nowdays the machine translation has been developed to overcome languagetranslation problems. Statistical machine translation is anapproach to machine translation with translation resultsgenerated on the basis of statistical models whereparameters are taken from the results of the analysis ofbilingual text corpus (parallel corpus). Parallel corpus is apair of corpus that contain sentences in a language and the translation. The goal of this research is to develop andimplement of statistical machine translation for translationfrom Indonesian into Sambas Malay and translation from Sambas Malay into Indonesian, and conduct testing toobtain the value of accuracy and quality of statisticalmachine translation, and also to conduct testing to obtainthe value of accuracy and quality of statistical machine translation. In this study are conducted two tests, the firstconducted tests on statistical machine translation of Indonesian into Sambas Malay translation and secondtest on statistical machine translation of Sambas Malay into Indonesian translation. On test 1 (Statistical Machine Translation of Indonesian to Sambas Malay) generate the value of BLEU score of 0.5555 or 55% while on Test 2(Statistical Machine Translation of Sambas Malay toIndonesian) produces BLEU score of 0.4950 or 49%.